Uncertainties of the solar wind in-situ velocity measurements - Gogoberidze, G.; Gorgaslidze, E.
We study spectral features of Alfvenic turbulence in fast solar wind. We propose a general, instrument independent method to estimate the uncertainty in velocity uctuations obtained by in-situ satellite observations in the solar wind. We show that when the measurement uncertainties of the velocity uctuations are taken into account the less energetic Elsasser spectrum obeys a unique power law scaling throughout the inertial range as prevailing theories of magnetohydrodynamic turbulence predict.
Keywords: Astronomy